2007
DOI: 10.1186/1471-2105-8-95
|View full text |Cite
|
Sign up to set email alerts
|

The reactive metabolite target protein database (TPDB) – a web-accessible resource

Abstract: Background: The toxic effects of many simple organic compounds stem from their biotransformation to chemically reactive metabolites which bind covalently to cellular proteins. To understand the mechanisms of cytotoxic responses it may be important to know which proteins become adducted and whether some may be common targets of multiple toxins. The literature of this field is widely scattered but expanding rapidly, suggesting the need for a comprehensive, searchable database of reactive metabolite target protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…It is therefore necessary to identify the subset of targets, i.e., covalently modified macromolecules, that are critical to the toxicological process. Unfortunately, although some liver proteins have been identified which are modified covalently by several xenobiotics (Hanzlik et al 2007), there are currently no techniques to predict the target macromolecule(s) for a particular chemically reactive metabolite let alone the biological consequences of a particular modification. However, from a simple chemical perspective, it is known that hard electrophiles generally react with hard nucleophiles, such as functional groups in DNA and lysine residues in proteins, whereas soft electrophiles react with soft nucleophiles, which include cysteine residues in proteins and in glutathione (Table 2), which has a concentration of approximately 10 mM in the liver.…”
Section: Relationship Between Metabolic Activation and Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore necessary to identify the subset of targets, i.e., covalently modified macromolecules, that are critical to the toxicological process. Unfortunately, although some liver proteins have been identified which are modified covalently by several xenobiotics (Hanzlik et al 2007), there are currently no techniques to predict the target macromolecule(s) for a particular chemically reactive metabolite let alone the biological consequences of a particular modification. However, from a simple chemical perspective, it is known that hard electrophiles generally react with hard nucleophiles, such as functional groups in DNA and lysine residues in proteins, whereas soft electrophiles react with soft nucleophiles, which include cysteine residues in proteins and in glutathione (Table 2), which has a concentration of approximately 10 mM in the liver.…”
Section: Relationship Between Metabolic Activation and Hepatotoxicitymentioning
confidence: 99%
“…The extent to which a particular loss of activity in vivo is due to adduction by a reactive metabolite or drug-induced oxidative modifications of amino acid residues is a complex analytical problem (Andringa et al 2008). Despite these difficulties, the expectation is that a comprehensive database of cellular proteins modified covalently by reactive metabolites in vivo should ultimately facilitate elucidation of the mechanisms of associated toxicities (Hanzlik et al 2007). It is already apparent that, although each bioactivated xenobiotic may modify a unique set of hepatic proteins, there is a partial commonality with the proteins modified by other compounds .…”
Section: Model Hepatotoxins: Role Of Reactive Metabolite Formationmentioning
confidence: 99%
“…Users can access the TPDB and conduct custom searches by chemical, target tissue, species, protein name, or combinations of these criteria. Since these search functions have been described previously (50) and are illustrated in the help function on the website, only one will be mentioned here, and that is the Commonality Matrix function (Table 2). On its diagonal this matrix shows the number of target proteins known for any given chemical (listed alphabetically on the row and column headings).…”
Section: The Reactive Metabolite Target Protein Databasementioning
confidence: 99%
“…Eighteen of the 25 proteins have known drug interactions in the Target Protein Database (38) (Supplemental File 8). An independent Gene Ontology (39) analysis also confirmed that a majority of the oxidized cysteines were located in mitochondrial and cytoplasmic proteins that are known to metabolize drugs and lipids (Supplemental File 8).…”
Section: Resultsmentioning
confidence: 99%